Advances in diagnosis and management of ovarian cancer - Farghaly, Samir A. (Springer US, 2014)
This volume is an up-to-date resource on the international state-of-the-art in the diagnosis and management of ovarian cancer.  While this devastating disease has been considered mainly a disease of the Western hemisphere, the book moves beyond our conventional understanding and embraces knowledge from around the world. It focuses on recent advances in diagnosis, including genetic screening; improvements and expanded choices in management, such as gene therapy and the optimization of chemotherapeutic agents; and the latest laparoscopic and robotic surgical techniques. Further chapters address histopathologic features of this disease,  and related psychosocial and quality of-life-issues. The book is aimed at the wide range of practitioners who care for patients with ovarian cancer and researchers who study the disease:  general surgeons, surgical oncologists, gynecological oncologists, medical oncologists, pediatric oncologists, gynecological pathologists, gynecologists, gynecological cancer epidemiologists, gynecological onco-psychologist, genetic counselors, geneticists, and cancer research scientists.